2020
DOI: 10.30773/pi.2020.0214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moderate Intensity Exercise on the Cortical Thickness and Subcortical Volumes of Preclinical Alzheimer’s Disease Patients: A Pilot Study

Abstract: Objective We aimed to explore the impact of moderate intensity exercise on the cortical thickness and subcortical volumes of preclinical Alzheimer’s disease (AD) patients.Methods Sixty-three preclinical AD patients with magnetic resonance imaging (MRI) and 18-florbetaben positron emission tomography (PET) data were enrolled in the study. Information on demographic characteristics, cognitive battery scores, self-reported exercise habits were attained. Structural magnetic resonance images were analyzed and proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…Our participants showed that their temporal meta-ROI cortical thickness decreased 0.94% in cycling and 1.54% for the stretching group over the 6-month intervention period, but the between-group differences were not significant. Two recent trials reported that aerobic exercise alone or in combination with cognitive training increased temporal meta-ROI cortical thickness in older adults with preclinical AD (Bae et al, 2020;Um et al, 2020). Our findings further show that over 12 months, temporal meta-ROI cortical thickness decreased 2.27% in the cycling group and 1.79% in the stretching group.…”
Section: Discussionsupporting
confidence: 82%
“…Our participants showed that their temporal meta-ROI cortical thickness decreased 0.94% in cycling and 1.54% for the stretching group over the 6-month intervention period, but the between-group differences were not significant. Two recent trials reported that aerobic exercise alone or in combination with cognitive training increased temporal meta-ROI cortical thickness in older adults with preclinical AD (Bae et al, 2020;Um et al, 2020). Our findings further show that over 12 months, temporal meta-ROI cortical thickness decreased 2.27% in the cycling group and 1.79% in the stretching group.…”
Section: Discussionsupporting
confidence: 82%
“…Long periods for relationships. Group analyses indicate activity over long periods can be related to cortical thickness [4,5,26,[28][29][30][31][32]. Consistent with these findings, in the studied individual, interactions extended over multi-week periods.…”
Section: Comparison Of the Present Individual-focused Concepts To Exi...supporting
confidence: 72%
“…Relationship bilaterality. Group-based work has reported relationships between physical activity and cortical thicknesses of both cortices [27,28,30,32]. Similarly, interactions were bilateral in the presently studied individual.…”
Section: Comparison Of the Present Individual-focused Concepts To Exi...mentioning
confidence: 60%
See 1 more Smart Citation
“…Although few studies focused on CT measures in relation to aerobic fitness, previous research has reported specific positive associations of VO 2 max with the GMV 43,66 and CT of the left STG 13,67 . Moreover, moderate-intensity aerobic training may slow down cortical thinning in several brain areas in patients with Alzheimer's Disease 68 , and mean CT is also positively related with physical activity habits in cognitively healthy individuals 69 . The beneficial effect of cardiorespiratory fitness on body composition, and specifically body fat reduction, has been proposed to mediate the positive relationship between fitness and mean CT, at least in developing children 70 .…”
Section: Discussionmentioning
confidence: 99%